One-step synthesis of CoAl2O4 inorganic pigment by solution combustion: The impact of fuel and ammonium nitrate - Chavarriaga, E. A.; Wermuth, Tiago Bender; Arcaro, Sabrina; García, Claudia; Ramirez, M. A. [UNESP]; Gómez, A.; Bezzon, Vinicius D.N.; Orlando, M. T.D.; Alarcón, J.; Bergmann, Carlos Pérez; Lopera, Alex A. (Elsevier, 2024)
Inorganic pigments are widely used in various industries, including ceramics and paints. CoAl2O4 is a highly stable pigment, but its industrial synthesis requires high temperatures, resulting in long synthesis times and high costs. Alternative synthesis routes have been proposed, but they are often expensive and require multiple thermal treatment stages. Solution combustion synthesis shows promise in reducing costs and synthesis time, but optimization is required so that synthesis is achieved in one step. In this work, we studied the problem of synthesizing the inorganic pigment CoAl2O4 using a single-step solution combustion synthesis. Therefore, the aim was to investigate the influence of different fuels: urea and citrulline, and the addition of an extra oxidizing agent, ammonium nitrate (A.N.), on the combustion temperature and the resulting structure, morphology, and colour of the pigment. The addition of A.N. resulted in a significant increase in the combustion temperature and the formation of crystalline CoAl2O4. The color coordinates for the powder following combustion, with the inclusion of 2 g of ammonium nitrate (A.N.) in the fuel mixture at an optimized O/F ratio of 0.5, were determined as follows: L* = 58.23, a* = −8.27, b* = −30.25, C*ab = −31.33, and h*ab = 263°, indicative of a blue hue. These results show that inorganic pigments could be used in ceramic decoration and acrylic paint. These findings are important for the development of new and efficient methods for synthesizing inorganic pigments with desirable properties for various applications.
Keywords: Ceramic decoration; CoAl2O4; Inorganic pigment; Pigment; Solution combustion synthesis